Vertical distribution and bacterial cell size and biomass in Lake Vanda, an Antarctic lake - Toshifumi Konda; Susumu Takii; Manabu Fukui; Yasushi Kusuoka; Genki I. Matsumoto; Shyu Nakaya; Tetsuya Torii (National Institute of Polar Research, 1987)
Vertical distribution of bacteria in Lake Vanda in the Dry Valleys region of the Antarctic was examined by the acridine orange direct count (AODC) method in December 1984 and the results were compared with those of January 1984 (S. TAKII et al. : Hydrobiologia, 135,15,1986). Bacterial numbers, cell sizes, and biomass in the water showed an almost identical pattern of vertical distribution at the two sampling times. Total bacteria by the AODC method were in the order of 10^4cells/ml in the water at the depth of 55m and above, and increased markedly to 5.0×10^6cells/ml in the bottom water (69m depth). Bacteria from the water between 5 and 60m depths were dominated by rods of 1.0-2.0μm length, and, particularly, filamentous bacteria more than 10μm long occurred a relatively high frequency in the water above the depth of 55m. On the other hand, most bacteria from the water at depths below 65m were coccoidal or short rods less than 1.0μm long. Bacterial biomass estimated from cell volumes ranged from 0.0026 to 0.079mgC/l.